Pediatric Gastroesophageal Reflux Clinical Practice Guidelines: Joint Recommendations of the North American Society for Pediatric Gastroenterology, Hepatology, and Nutrition and the European Society for Pediatric Gastroenterology, Hepatology, and Nutrition. Issue 3 (March 2018) - Rosen, Rachel; Vandenplas, Yvan; Singendonk, Maartje; Cabana, Michael; DiLorenzo, Carlo; Gottrand, Frederic; Gupta, Sandeep; Langendam, Miranda; Staiano, Annamaria; Thapar, Nikhil; Tipnis, Neelesh; Tabbers, Merit
Abstract : ABSTRACT: This document serves as an update of the North American Society for Pediatric Gastroenterology, Hepatology, and Nutrition (NASPGHAN) and the European Society for Pediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) 2009 clinical guidelines for the diagnosis and management of gastroesophageal reflux disease (GERD) in infants and children and is intended to be applied in daily practice and as a basis for clinical trials. Eight clinical questions addressing diagnostic, therapeutic and prognostic topics were formulated. A systematic literature search was performed from October 1, 2008 (if the question was addressed by 2009 guidelines) or from inception to June 1, 2015 using Embase, MEDLINE, the Cochrane Database of Systematic Reviews and the Cochrane Central Register of Controlled Clinical Trials. The approach of the Grading of Recommendations Assessment, Development and Evaluation (GRADE) was applied to define and prioritize outcomes. For therapeutic questions, the quality of evidence was also assessed using GRADE. Grading the quality of evidence for other questions was performed according to the Quality Assessment of Studies of Diagnostic Accuracy (QUADAS) and Quality in Prognostic Studies (QUIPS) tools. During a 3-day consensus meeting, all recommendations were discussed and finalized. In cases where no randomized controlled trials (RCT; therapeutic questions) or diagnostic accuracy studies were available to support the recommendations, expert opinion was used. The group members voted on each recommendation, using the nominal voting technique. With this approach, recommendations regarding evaluation and management of infants and children with GERD to standardize and improve quality of care were formulated. Additionally, 2 algorithms were developed, 1 for infants <12 months of age and the other for older infants and children. Abstract : Supplemental Digital Content is available in the text